<h3>
Answer: Yes they are equivalent</h3>
==============================================
Work Shown:
Expand out the first expression to get
(a-3)(2a^2 + 3a + 3)
a(2a^2 + 3a + 3) - 3(2a^2 + 3a + 3)
2a^3 + 3a^2 + 3a - 6a^2 - 9a - 9
2a^3 + (3a^2-6a^2) + (3a-9a) - 9
2a^3 - 3a^2 - 6a - 9
Divide every term by 2 so we can pull out a 2 through the distributive property
2a^3 - 3a^2 - 6a - 9 = 2(a^3 - 1.5a^2 - 3a - 4.5)
This shows that (a-3)(2a^2 + 3a + 3) is equivalent to 2(a^3 - 1.5a^2 - 3a - 4.5)
1. 5 and E, 6 and F, 7 and D, 8 and A, 9 and G
Answer:
8
Step-by-step explanation:
6 divided by.75 if u think I'm wrong check and correct me
Answer:
3b(3a+7c) i used mathpapa.com
Answer:
-5/9
Step-by-step explanation:
also for this one, you have to put x as 3, y as 4, and z as 1
4/3(3)-1
=4/9-1
=4/9-9/9
=-5/9
hope this helps xD